ATTEMPTS TO RETAIN THE IDENTITIES IN THE ENGLISH TRANSLATION OF AHMAD TOHARI’S “SENYUM KARYAMIN” - Harris Hermansyah Setiajid (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2020)
In its function as a bridge to help people of different languages understand each other, translation seems toencounter more and more challenges. Although it looks like an innocent job, translation is an overlycomplex undertaking, and sometimes dangerous. It is fully charged with interest in any step of its process.Identity, especially nowadays, has come at center stage in the discussion about culture. People with differentidentities will get annoyed when they receive treatment, or sometimes harassment, from the majority. Atranslation that should have a noble objective, i.e. bridging the gap between people, now has its obstacle.Identity loss in translation, however, inevitably happens. Some identity items of source text can beexpressed aptly into the target text, and some others may lose during the process of translation. Such aphenomenon is rather common in translation, particularly when the translators are unable to apply the rightstrategy to minimize such loss. This paper tries to look at cultural loss in the English translation of Tohari'sshort story "Senyum Karyamin" which was translated into "Karyamin's Smile". It is found that thetranslator's inability to render cultural contents into English indicates the tendency to take readily availableterms, which eventually oversimplifies the translation and loses the cultural identity inherent in the sourcetext.